Artificial intelligence-supervised vectorcardiography for the diagnosis of a young adult with abnormal origin of the right coronary artery from aorta - Özyüksel, Arda; Salatzki, Janek; Steen, Henning (Cardiology in the young, 2024)
Coronary anomalies occur in 0.2% to 1.2% of the population, with the anomalous aortic origin of the coronary arteries accounting for one third of these cases. Clinical presentations can vary from asymptomatic to experiencing cardiac symptoms and sudden death, making diagnosis challenging. In this report, we present a novel artificial intelligence-supervised vectorcardiographic analysis and the subsequent successful surgical treatment of a young patient.